The interrelations between artificial intelligence (AI) usage and academic performance - Chin, Wie Jane (2024)
With the increasing prevalence of integrating Artificial Intelligence (AI) into the education sector, educators and administrators are positioned to be equipped with an extensive grasp of the possibilities for AI in education. Previous studies have mostly concentrated on technology tools, algorithms, validation, and utilisation rather than their impact on student performance. As such, the focus on learning outcomes tends to remain limited. This paper intends to bridge the gap by studying how different types and extents of the use of AI may affect how students do in school, especially within higher education institutions. Six different uses of AI, routine use, regular use, efficient use, extended use, innovative use and reinformed use, were selected to look into their effect on students’ academic performance. A survey was designed and distributed to higher education students. Partial least square structural equation modelling (PLS-SEM) was adopted for studying the associations between the six AI usages and students’ academic performance. The results suggested that four of the six constructs were the primary drivers of academic achievement. In accordance with the PLS predict analysis, the research model nevertheless retained predictive potential in representing the findings that were observed. The outcomes of this paper offered useful insights for academicians and practioners to improve the incorporation of AI in education strategically, while also setting a sturdy foundation for further investigation into the impact of using AI on academic performance.